KEBIJAKAN PELAYANAN KESEHATAN REPRODUKSI REMAJA - Joyce S.H. Djaelani (Populasi, 1997)
Indonesian adolescents are 37 per cent of the total of population of this country. The large quantity, however, is comparatively unequal to the right of reproduction health service they receive. They are often seen in the position as an "isolated tribe". Consequently, not only few adolescents, especially the female ones become victims of "Mimi Momo". This writing begins with a description of a case related to the reproduction health hitting an adolescent, then besides being related to the Cairo action program, it is also correlated with the recommendation on the policies of the reproduction service for adolescents.